FORMATION OF COGNITIVE INDEPENDENCE OF STUDENTS OF ECONOMIC DIRECTION OF TRAINING IN THE PROCESS OF STUDYING PROFESSIONAL DISCIPLINES (Pedagogy of Higher and Secondary Education, 2022)
The article deals with some actual problems concerning the formation o f students’ (are being trained to be economists) cognitive self directed activities in the process o f special disciplines studies.